Dampak Pembiayaan Terhadap Kinerja Keuangan Bank Umum Syariah Tahun 2016-2020 - Mufti Arief Arfiansyah; Yogi Kurniawan; Catur Nugroho (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2022)
Financial performance analysis is used to look at how good financial performance is by observing the correct financial performance provisions. The study deals with buying and selling financing (X_1) and profit sharing financing (X_2) on the financial performance of Islamic commercial banks (BUS). The study uses Return on Equity (Y) as a measure of financial performance. This research approach is quantitative with the aim of examining the impact of buying and selling financing as well as the results on BUS performance. The sampling method uses purposive sampling. Samples that met the standards were 12 BUS samples within 5 years from 2016 to 2020. The research used the E-Views application. The information analysis used is multiple linear regression analysis. The results of the study are (1) Buying and selling financing affects the profitability of Return On Equity (ROE). (2) Profit sharing financing affects ROE profitability. (3) Buying and selling financing and profit sharing financing jointly affect ROE profitability. Buying and selling financing and profit sharing financing affect ROE profitability, meaning that if buying and selling financing and profit sharing channeled by BUS continue to increase, ROE profitability also increases. Therefore, Islamic commercial banks should continue to increase the distribution of buying and selling financing and profit sharing financing to the public.